2017
DOI: 10.1103/physrevlett.119.056001
|View full text |Cite
|
Sign up to set email alerts
|

Length-Scale Dependence of the Stokes-Einstein and Adam-Gibbs Relations in Model Glass Formers

Abstract: The Adam-Gibbs (AG) relation connects the dynamics of a glass-forming liquid to its the thermodynamics via. the configurational entropy, and is of fundamental importance in descriptions of glassy behaviour. The breakdown of the Stokes-Einstein (SEB) relation between the diffusion coefficient and the viscosity (or structural relaxation times) in glass formers raises the question as to which dynamical quantity the AG relation describes. By performing molecular dynamics simulations, we show that the AG relation i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 57 publications
3
35
0
Order By: Relevance
“…using thermodynamic integration, where F ex is the excess Helmholtz free energy, and U ex ≡ U is the potential energy. Application of thermodynamic integration to supercooled liquids is standard 6,34,38 . First, a path at a high temperature T ref above the critical point was chosen, integrating the equation…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…using thermodynamic integration, where F ex is the excess Helmholtz free energy, and U ex ≡ U is the potential energy. Application of thermodynamic integration to supercooled liquids is standard 6,34,38 . First, a path at a high temperature T ref above the critical point was chosen, integrating the equation…”
Section: Methodsmentioning
confidence: 99%
“…The Stokes-Einstein (SE) relation connects the diffusion coefficient D of a large particle immersed in a solvent with viscosity η, predicting that D ∝ η −1 T. The SE relation breaks down in the supercooled regime and explanations have been presented from various theoretical perspectives 33,38,[63][64][65][66][67][68][69][70] . Flenner et al 68 obtained a good collapse of the diffusion coefficient plotted against the structural relaxation time (which may be used as a proxy for the viscosity) for supercooled binary mixtures by scaling the diffusion coefficient and the relaxation time.…”
mentioning
confidence: 99%
“…* yylu@ciac.ac.cn † ljan@ciac.ac.cn ‡ zgw@caltech.edu Another anomalous behavior in the glass-forming liquids is the breakdown of the Stokes-Einstein (SE) relation, which relates the self-diffusion coefficient D to the viscosity or equivalently to the relaxation time τ α [9][10][11][12]. While for normal liquids the product Dτ α is temperature-independent, numerous studies [13][14][15][16][17][18][19] in recent decades have shown that this relation is violated in glass-forming liquids at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [27], it is shown that if one calculates the wave-vector dependent α-relaxation time, τ α (q) in the supercooled temperature regime, then one finds that Stokes-Einstein relation does not break down above a characteristic wave vector, q * which depends on the studied temperature, T . The inverse of this characteristic wave vector defines a length scale, ξ * (T ) = 2π/q * (T ).…”
Section: Introductionmentioning
confidence: 99%